(untitled) (Global Conference on Medical and Health Sciences, 2026)
This literature review provides a comprehensive analysis of the prevalence of emotional burnout syndrome (EBS) among healthcare workers, its contributing factors, and its impact on interpersonal relationships. Contemporary epidemiological data indicate that burnout is highly prevalent, affecting approximately 30–60% of healthcare professionals. The findings demonstrate that emotional exhaustion, depersonalization, and reduced personal accomplishment represent the core components of the syndrome. Furthermore, EBS extends beyond the workplace, adversely influencing family and social relationships and increasing the risk of depression and suicidal ideation. The analysis highlights that emotional burnout is not only an individual issue but also a systemic challenge within healthcare systems. Therefore, the development and implementation of comprehensive preventive and organizational strategies aimed at reducing burnout are of critical importance.